2021
DOI: 10.3389/fmed.2021.769845
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated COVID-19 Vaccine Induces a Low Humoral Immune Response in a Subset of Dermatological Patients Receiving Immunosuppressants

Abstract: Inactivated Sinovac-CoronaVac vaccine (Sinovac Life Sciences, Beijing) for coronavirus disease 2019 (COVID-19) has been used in many countries. However, its immunogenicity profile in immunosuppressed dermatological patients is lacking. This prospective observational case-control study compared the humoral immune response between adult dermatological patients receiving systemic immunosuppressive therapies (n = 14) and those who did not (n = 18); excluding patients with HIV infection, cancer, non-dermatological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Of 6 individuals who did not have detectable antibodies, 4 were receiving JAKi monotherapy or combination therapy, 1 methotrexate/prednisolone co-therapy and 1 methotrexate/prednisolone co-therapy. Neutralising A neutralising humoral response was detected in 13/16 (81%) individuals on standard systemic therapy, 17/18 (94%) on cytokine targeted biologic therapy, 4/5 (80%) on abatacept, and 8/12 (67%) on JAKi therapy Ruddy et al [ 37 ] Rheumatological disease (n = 404) including RA, ankylosing spondylitis, PsA, reactive arthritis, SLE, Sjogren’s syndrome, myositis, systemic sclerosis and vasculitis No controls Median age: 44 years Gender: 385 (96%) female Ethnicity: 367 (91%) White Standard systemic Azathioprine, ciclosporin, dimethyl fumarate, hydroxychloroquine, leflunomide, methotrexate, mycophenolate mofetil, sirolimus, sulfasalazine and tacrolimus Targeted Abatacept, anakinra, belimumab, guselkumab, IL-6i, IL-17i, JAKi, rituximab, TNFi and ustekinumab BNT162b2 (198/404, 49%) mRNA-1273 (204/404, 51%) N/A Humoral Seroconversion 378/404 (94%) of individuals with rheumatological disease seroconverted at a median of 29 days after 2nd dose A greater proportion of those receiving TNFi had detectable antibodies (100%), vs those receiving mycophenolate (73%, p < 0.001), rituximab (26%, p < 0.001) or glucocorticoids (82%, p < 0.001) or those with a diagnosis of myositis (79%, p = 0.01) Lower median antibody titres in individuals receiving mycophenolate mofetil (8 U/mL) and rituximab (< 0.4 U/mL) vs individuals receiving glucocorticoid monotherapy (> 250 U/mL) Seree-aphinan et al [ 38 ] Cases: Individuals with pemphigus, psoriasis and chronic spontaneous urticaria who are receiving immune-modifying therapy ( n = 14) Controls: individuals (with acne, melasma, androgenetic alopecia, seborrheic keratosis) who are not receiving immune-modifying therapy ( n = 18) Mean age: Controls – 45 years Cases – 44 years Gender: Controls – 11 (61%) female Cases – 10 (71%) female Ethnicity: Not included Standard systemic Azathioprine, ciclosporin, methotrexate, mycophenolate mofetil and prednisone Targeted Ixekizumab, omalizumab and secukinumab CoronaVac (Sinovac) N/A Humoral Seroconversion No individuals (0/6, 0%) taking azathioprine, ciclosporin, mycophenolate mofetil, or moderate-to-high dose corticosteroids seroconverted 4 weeks post-second vaccine. 7/8 (87.5%) individuals on low dose methotrexate, low d...…”
Section: Results: Summary Of Findings From Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 6 individuals who did not have detectable antibodies, 4 were receiving JAKi monotherapy or combination therapy, 1 methotrexate/prednisolone co-therapy and 1 methotrexate/prednisolone co-therapy. Neutralising A neutralising humoral response was detected in 13/16 (81%) individuals on standard systemic therapy, 17/18 (94%) on cytokine targeted biologic therapy, 4/5 (80%) on abatacept, and 8/12 (67%) on JAKi therapy Ruddy et al [ 37 ] Rheumatological disease (n = 404) including RA, ankylosing spondylitis, PsA, reactive arthritis, SLE, Sjogren’s syndrome, myositis, systemic sclerosis and vasculitis No controls Median age: 44 years Gender: 385 (96%) female Ethnicity: 367 (91%) White Standard systemic Azathioprine, ciclosporin, dimethyl fumarate, hydroxychloroquine, leflunomide, methotrexate, mycophenolate mofetil, sirolimus, sulfasalazine and tacrolimus Targeted Abatacept, anakinra, belimumab, guselkumab, IL-6i, IL-17i, JAKi, rituximab, TNFi and ustekinumab BNT162b2 (198/404, 49%) mRNA-1273 (204/404, 51%) N/A Humoral Seroconversion 378/404 (94%) of individuals with rheumatological disease seroconverted at a median of 29 days after 2nd dose A greater proportion of those receiving TNFi had detectable antibodies (100%), vs those receiving mycophenolate (73%, p < 0.001), rituximab (26%, p < 0.001) or glucocorticoids (82%, p < 0.001) or those with a diagnosis of myositis (79%, p = 0.01) Lower median antibody titres in individuals receiving mycophenolate mofetil (8 U/mL) and rituximab (< 0.4 U/mL) vs individuals receiving glucocorticoid monotherapy (> 250 U/mL) Seree-aphinan et al [ 38 ] Cases: Individuals with pemphigus, psoriasis and chronic spontaneous urticaria who are receiving immune-modifying therapy ( n = 14) Controls: individuals (with acne, melasma, androgenetic alopecia, seborrheic keratosis) who are not receiving immune-modifying therapy ( n = 18) Mean age: Controls – 45 years Cases – 44 years Gender: Controls – 11 (61%) female Cases – 10 (71%) female Ethnicity: Not included Standard systemic Azathioprine, ciclosporin, methotrexate, mycophenolate mofetil and prednisone Targeted Ixekizumab, omalizumab and secukinumab CoronaVac (Sinovac) N/A Humoral Seroconversion No individuals (0/6, 0%) taking azathioprine, ciclosporin, mycophenolate mofetil, or moderate-to-high dose corticosteroids seroconverted 4 weeks post-second vaccine. 7/8 (87.5%) individuals on low dose methotrexate, low d...…”
Section: Results: Summary Of Findings From Literature Searchmentioning
confidence: 99%
“…In ten studies where neutralisation was investigated [ 23 , 25 27 , 29 , 34 •, 36 , 38 , 40 , 41 ], the majority of individuals receiving immune-modifying therapy developed a neutralising response after the second vaccine dose (range 63–100%, with the exception of those receiving rituximab); however, neutralisation titres were lower compared to healthy controls in 3 studies [ 27 , 29 , 38 ]. Our own study (individuals with psoriasis, n = 67; healthy controls, n = 15) showed that all study participants had detectable neutralising antibodies against wild-type, Alpha and Delta SARS-CoV-2 variants following the second vaccine dose, and there were higher neutralising antibody titres after the second dose compared to the first [ 34 •].…”
Section: Immune Response To the 2nd Dose Of Covid-19 Vaccinementioning
confidence: 99%
“…It has been shown that immunosuppressive drugs reduce the efficacy of SARS-CoV2 vaccines ( 31 ). Patients with immune-mediated skin conditions treated with immunosuppressants had low levels of serum anti-SARS-CoV-2 IgG antibodies, according to a recent study ( 32 ). The higher doses of corticosteroids in patients with active disease would attenuate the response to the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…16 Lastly, focusing on mechanism of action, anti-PD-1 or PD-L1 may modulate humoral immunity which enhances pre-existing autoantibodies and unmask latent auto-immunity. [17][18][19] Therefore, anti-PD-L1 might be involved with immune-related adverse events, not only by increasing the activity of the immune system against antigens in both cancers and healthy tissue, but also by increasing levels of pre-existing autoantibodies. These mechanisms may explain the positive autoantibodies in our case.…”
Section: Dovepressmentioning
confidence: 99%